2016
DOI: 10.1074/jbc.m115.704288
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Rafts on Airway Epithelial Cells

Abstract: Many cells, including murine airway epithelial cells, respond to a variety of inflammatory stimuli by synthesizing leukocyteadhesive hyaluronan (HA) cables that remain attached to their cell surfaces. This study shows that air-liquid interface cultures of murine airway epithelial cells (AECs) also actively synthesize and release a majority of their HA onto their ciliated apical surfaces to form a heavy chain hyaluronan (HC-HA) matrix in the absence of inflammatory stimuli. These matrices do not resemble the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
1
13
1
Order By: Relevance
“…34, 35 Recently, Abbadi et al reported that lung epithelial cells also synthesize cell surface glycocalyx of HC3-HA (HA-Raft) that traps leukocytes; thus, it might have a role in host defense. 36 Our observation of the presence of the HC-HA/PTX3 complex on UMSCs is consistent with the idea that such complexes may account for the ability of UMSCs to modulate host inflammation and immune responses.…”
Section: Use Of Umsc and Bmsc For Treating Congenital Corneal Diseases‡supporting
confidence: 89%
“…34, 35 Recently, Abbadi et al reported that lung epithelial cells also synthesize cell surface glycocalyx of HC3-HA (HA-Raft) that traps leukocytes; thus, it might have a role in host defense. 36 Our observation of the presence of the HC-HA/PTX3 complex on UMSCs is consistent with the idea that such complexes may account for the ability of UMSCs to modulate host inflammation and immune responses.…”
Section: Use Of Umsc and Bmsc For Treating Congenital Corneal Diseases‡supporting
confidence: 89%
“…Constitutive HC•HA formation is associated with murine airway epithelial cells (AECs) and human renal proximal tubular ECs, both of which make HC3•HA, through constitutively expressing PI and TSG-6 [110]. AECs in culture assemble the HC3•HA complexes into raft-like structures on their ciliated apical surface that can capture and entrap leukocytes.…”
Section: The Role Of Tsg-6 In Hc•ha Formation 421 the Structural And Functional Diversity Of Hc•hasmentioning
confidence: 99%
“…Type II alveolar epithelial cells (AECs) express HAS2 and surface HA ( 17 ). HA is loosely attached and shed from the apical surface of primary AEC cultures, and can be observed above the airway epithelium ( 18 ), although this is not always the case ( 10 , 12 ). This suggests that HA can be released into the alveolar fluid above the AECs.…”
Section: Hyaluronan In the Healthy Lungmentioning
confidence: 99%